Mining the ocean floor vs mining the Moon: what can we learn from our past experiences? - Pelton, Joseph N.; Mishra, Nishith; Elia Vitoloni, Martina (Frontiers in Space Technologies, 2025)
This perspective piece examines the parallels and distinctions between ocean floor mining and potential lunar extraction, emphasizing the necessity of protecting the Moon as a global common. It traces the historical evolution of global commons governance, highlighting key international treaties that have shaped the management of shared resources. The analysis delves into the practical implementation challenges of maintaining equitable access and environmental sustainability in both terrestrial and extraterrestrial contexts. Through a case study of the Pacific Ocean seabed mining initiative by Nauru Ocean Resources Inc., the paper illustrates the complexities and controversies surrounding resource exploitation in recognized global commons and common heritage areas. It underscores the inadequacies of current legal frameworks, such as the Moon Agreement and the Law of the Sea, in addressing emerging technological and geopolitical dynamics. The discussion extends to the unique challenges posed by celestial bodies like the Moon and asteroids, advocating for tailored regulatory mechanisms that consider their distinct environmental and regenerative capacities. Last, this perspective piece argues that without just and equitable regulatory decisions in ocean mining, similar oversights are likely in lunar endeavours, thereby jeopardizing the sustainable and fair utilization of outer space resources.